Estimation of Carbon Dioxide and Carbon Stock of Vegetation along the Sukarno-Hatta Street Sides - Fatma M Omar Abobsesa; Arief Rachmansyach; Amin Setyo Leksono (Graduate Program, 2018)
Carbon dioxide (CO2) is an essential element of the atmosphere that is the basis of photosynthesis process and the vital component of body organism processes. However, if it rises above the normal level, it becomes the most serious cause of global warming. However, the growth of CO2 in the atmosphere has been slowed by the increase in the ability of plants to absorb the gas. This study is aimed to analyze CO2 emissions and plant absorption ability to discover carbon stock and carbon balance in the atmosphere. This study used a sample of human activities that contribute to CO2 emissions along the Soekarno-Hatta Street and the number of trees that soak the emissions. Remote sensing is applied to predict the levels of carbon dioxide emissions and absorption and carbon stocks. The absorption and stock of the carbon are calculated using a specific formula for biomass. The results showed a significant amount of carbon dioxide was emitted by motor vehicles passing through Soekarno-Hatta Street. However, only a small portion was generated by human activities carried out in stores, offices, restaurants, hotels, and hospitals. In line with that, the trees in the Soekarno-Hatta area were able to absorb carbon dioxide about 6 times higher than emitted. It also proved that the Palm tree (Roystonea regia) was capable of storing more carbon dioxide in significant amounts than the other two species, the Ashoka tree (Polyalthia longifolia), and the Rain tree (Samanea saman). Therefore, increasing the number of trees such as Palm tree in the area was recommended.Keywords: Coaching strategy, Regency Adiwiyata, School management, Sintang Regency